Du journalisme comme une mésoépistémologie - Bertrand Labasse (Communication)
Journalism developed in response to the need for a mediator between the state of the world and people wanting to stay abreast of it. But this role is increasingly weakened today by the commoditization of information technology and cannot fully explain how journalism frames reality. The author takes the view that journalism is one possible way of obtaining and communicating information. As such, it lies halfway between everyday perceptions of reality and the epistemology of legitimized forms of knowledge production. The author first examines the emergence and evolution of French-language journalistic standards, then examines them in relation to the principles of more formal knowledge-generating systems.